21-Gene recurrence score predictive for prognostic benefit of radiotherapy in patients age ≥ 70 with T1N0 ER/PR + HER2- breast cancer treated with breast conserving surgery and endocrine therapy. (September 2022) - Chevli, Neil; Haque, Waqar; Tran, Kevin T.; Farach, Andrew M.; Schwartz, Mary R.; Hatch, Sandra S.; Butler, E. Brian; Teh, Bin S.
Highlights: In modern practice, patients age ≥70 with T1N0 ER/PR + HER2- breast cancer who are treated with breast conserving surgery and endocrine therapy have been considered candidates for omission of radiotherapy. Recurrence score (RS) is predictive for prognostic benefit of radiotherapy in patients age ≥70 years. There is an overall survival benefit with the use of radiotherapy in patients with RS ≥11 but not in patients with RS < 11. Assessment of RS in patients age ≥70 years is recommended with consideration of RT when RS is ≥11. Abstract: Purpose: Based on the results of the Cancer and Leukemia Group B (CALGB) 9343 trial, patients age ≥70 with T1N0 hormone receptor positive (ER/PR+), human epidermal growth factor receptor-2 negative (HER2-) breast cancer who are treated with breast conserving surgery (BCS) and endocrine therapy (ET) are candidates for omission of radiotherapy (RT). Because the CALGB 9343 trial did not stratify based on recurrence score (RS) test (Oncotype Dx), we conducted the present retrospective study to determine whether RS is predictive of who may benefit from RT following BCS in this cohort. Materials and methods: The National Cancer Database (NCDB) was queried (2004–2017) for patients age ≥ 70 with pT1N0 ER+/PR + HER2- breast cancer treated with BCS and ET. Patients were stratified based on their RS (low risk [LR] = 1–10, intermediate risk [IR] = 11–25, high risk [HR] = 26–99). Propensity score matching (PSM) created 1:1 matched cohorts of patients who received radiotherapy and those who did not. Kaplan-Meier analysis evaluated overall survival (OS). Univariable (UVA) and multivariable (MVA) Cox proportional hazard analyses identified clinical and treatment factors prognostic for OS. Results: A total of 11, 891 patients met the selection criteria: 3364 in the LR cohort, 7305 in the IR cohort, and 1222 in the HR cohort. A total of 79 % received RT: 77 % in the LR cohort, 79 % in the IR cohort, and 85 % in the HR cohort. Because PSM could not be efficiently performed in the HR cohort alone, the IR and HR cohort were merged (IRHR) for matching. After PSM, the 5-year OS in the LR cohort was 91 % for those who received RT and 89 % for those who did not ( p  = 0.605). In the IRHR cohort, the 5-year OS was 91 % for those who received RT and 87 % for those who did not ( p  = 0.003). On MVA in the LR cohort, RT ( p  = 0.727) was not predictive of improved OS. On MVA in the IRHR cohort, RT ( p  = 0.010) was a positive prognostic factor for OS. Conclusion: In this older cohort of patients, there is an OS benefit with the use of RT in patients with IRHR RS but not in patients with LR RS. Pending prospective evaluation, assessment of RS in this older subset of patients is recommended with consideration of RT when RS is ≥11.